Inter-field strength agreement of left atrial assessment at 1.5T and 3T. (3rd October 2022) - Alfuhied, A; Ayton, S; Gulsin, G S; Parke, K S; Wormleighton, J V; Moss, A; Graham-Brown, M P M; Arnold, J R; McCann, G P; Singh, A
Abstract: Background: The agreement of left atrial (LA) volumetric and strain parameters between 1.5 and 3-tesla cardiovascular magnetic resonance (CMR) is not known. We aimed to investigate inter-field strength agreement of LA measurements in healthy volunteers scanned at both field strengths on the same day. Methods: 22 healthy volunteers were prospectively recruited and randomized to undergo scanning at either 1.5T or 3T first, immediately crossing over to the other field strength and scanned by the same radiographer. Steady-state free precession cines were analyzed blinded using Medis Suite. LA volumes and LA emptying fraction (LAEF) were calculated using the biplane area length method. LA strain (LAS) was assessed on 4- and 2-chamber and average values were calculated for LA reservoir, conduit, and booster pump function. Data were compared with paired t-tests and agreement was assessed by Bland-Altman plots and intra-class correlation coefficients (ICC). Results: The median age was 32.5 (IQR 27.5, 42.5) and 45% were male. Key results are shown in the table and figure. There were no significant differences in the LA volumetric or strain mean values between 1.5T and 3T, although Bland-Altman analysis demonstrated a slightly positive bias at 1.5T for LAVmax, LAEF and LAS parameters. The inter-field strength agreement was excellent for LA volumes, reservoir and conduit strain (ICC >0.85, p<0.001), whilst LAEF showed good agreement (ICC=0.77, p=0.001). LAS at booster pump showed poor agreement, with the lowest ICC. The limits of agreement on Bland-Altman analysis were comparable for LAEF and LAS at reservoir. Conclusion: There was excellent inter-field strength agreement for LA volumes, reservoir and conduit strain, suggesting that measurements can be used interchangeably between field strengths. Booster pump LAS had poor agreement, which is likely due to the fact that this measurement is less reproducible than volumes and reservoir/conduit LAS. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): National Institute for Health Research (NIHR)